Biological Strategies to Enhance Healing of the Avascular Area of the Meniscus. (13th December 2011) - Longo, Umile Giuseppe; Campi, Stefano; Romeo, Giovanni; Spiezia, Filippo; Maffulli, Nicola; Denaro, Vincenzo
Abstract : Meniscal injuries in the vascularized peripheral part of the meniscus have a better healing potential than tears in the central avascular zone because meniscal healing principally depends on its vascular supply. Several biological strategies have been proposed to enhance healing of the avascular area of the meniscus: abrasion therapy, fibrin clot, organ culture, cell therapy, and applications of growth factors. However, data are too heterogeneous to achieve definitive conclusions on the use of these techniques for routine management of meniscal lesions. Although most preclinical and clinical studies are very promising, they are still at an experimental stage. More prospective randomised controlled trials are needed to compare the different techniques for clinical results, applicability, and cost-effectiveness.